Economic feasibility of calcium looping under uncertainty - Supporting Information - Hanak, Dawid P.; Manovic, Vasilije (Cranfield University, 2017)
Supporting information to Economic feasibility of calcium looping under uncertainty.
Keywords: 'uncertainty problem'; 'Probabilistic Models'; 'Process modelling'; 'techno-economic analysis'; 'Carbon Capture Engineering (excl. Sequestration)'; 'Power and Energy Systems Engineering (excl. Renewable Power)'